REDESAIN BAHAN AJAR UNTUK MENINGKATKAN KETERAMPILAN BERBICARA BAHASA ARAB BAGI PESERTA DIDIK MADRASAH ALIYAH NEGERI - Satrio Satrio (Profetika: Jurnal Studi Islam, 2021)
Learning resources are one of the most important aspects of learning, the achievement of learning objectives is also inseparable from the learning resources used. In line with that, several studies prove that the arabic learning resources used in Indonesia have not been clearly measured the orientation of targeted language skills, therefore this study is designed to find the right form of design for Arabic language teaching materials in an effort to improve the speaking ability of learners. The methods used in this study are qualitative, data collection techniques used observation, interview and documentation, data analysis techniques using the approach used by Haberman. The results prove that the design of Arabic teaching materials for the purpose of speaking skills should be dominated by conversational exercises, tadribat with various models, maximizing grammatical examples that are applicative.